MICROMANOMETRO INTRACARDIACO. PRINCIPIOS DO METODO, VANTAGENS E DESVANTAGENS EM RELACAO A MANOMETRIA CONVENCIONAL - Tucci, P. J.F.; Cicogna, A. C.; Spadaro, J. (My University, 1974)
The authors describe the working principles of Telco's micromanometer. They discuss its advantages and disadvantages as compared to the conventional pressure measurement techniques and the value of the method when a high fidelity left ventricular pressure is needed. Some disadvantages of the common catheterization technique, due to the liquid column of the system, are pointed out.
Intracardiac micromanometer. Its principles, advantages and disadvantages in relation to the conventional manometer